Technique et esthétique de la bague dans l’architecture gothique du Nord de la France au xiie siècle - Arnaud Timbert (Archéologie Médiévale)
Rings constitute one of the main characteristics of twelfth century Gothic architecture in the north of France. Their presence is a result of the common use of monolithic supports during this period. The rings indeed reinforce the shafts en délit between themselves – and from the walls against which they are positioned – whilst playing the role of a reserve and a shock absorber when the walls settle, thus preventing the monolithic shafts from shattering. Beyond this technical aspect, they also participate in the architectural composition, by imposing intentional ternary rhythms that often contribute to the nuanced individualization of space characteristic of the style of the first Gothic architecture.